The Alberta climate dialogue as integrative education: deliberative democracy meets climate change - Siddiqui, Asif (My University, 2013)
Topics: Alberta Climate Dialogue (ABCD), ABCD as Integrative Education, First Social Network–Students, Second Social Network–Edmonton Citizens Panel, Third Social Network–Greater Business Involvement (Future Work).
Presented on June 8, 2013 at the 19th Annual International Symposium on Society and Resource Management: A Time for Integration held at the YMCA of the Rockies in Estes Park, United States.
Keywords: deliberative democracy; climate